THE EFFECT OF FENOFIBRATE ON THE DEVELOPMENT OF DIABETIC RETINOPATHY AND NEPHROPATHY – A REVIEW OF CURRENT RESEARCH - Kacper Szeląg; Anna Opalińska; Cezary Lubas; Paula Folta; Joanna Kłosowska; Karolina Błądzińska; Maciej Błądziński; Małgorzata Zach; Piotr Świerczek; Antoni Kujawski (International Journal of Innovative Technologies in Social Science, 2025)
The aim of this review is to summarize current knowledge on the effect of fenofibrate in reducing the risk and progression of two major diabetes complications: retinopathy and kidney disease. We also discuss the mechanisms underlying fenofibrate’s potential protective effects and the pathophysiology of these complications.A literature search was conducted in PubMed and Google Scholar, with emphasis on publications from 2020–2025. The search strategy included terms such as “fenofibrate diabetes,” “fenofibrate nephropathy,” “fenofibrate retinopathy,” “diabetic kidney disease,” and “diabetes dyslipidemia.”Diabetes mellitus affects over 537 million people worldwide, reducing quality of life and creating a major healthcare burden. Fenofibrate, a fibrate-class lipid-lowering agent, has gained attention due to its frequent use in patients with diabetes and dyslipidemia. Evidence suggests that fenofibrate may slow the progression of diabetic retinopathy, reducing the need for surgical interventions, and may also decrease albuminuria and delay the progression of diabetic kidney disease.In conclusion, fenofibrate appears to have potential as an adjunct therapy for preventing microvascular complications of diabetes, although further research is required to confirm its long-term benefits.